2015
DOI: 10.1002/adma.201503202
|View full text |Cite
|
Sign up to set email alerts
|

Memristive Physically Evolving Networks Enabling the Emulation of Heterosynaptic Plasticity

Abstract: A nanoscale, solid-state physically evolving network is experimentally demonstrated, based on the self-organization of Ag nanoclusters under an electric field. The adaptive nature of the network is determined by the collective inputs from multiple terminals and allows the emulation of heterosynaptic plasticity, an important learning rule in biological systems. These effects are universally observed in devices based on different switching materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 33 publications
4
145
1
Order By: Relevance
“…The distant parts of the dendrites of excitatory neurons in the brain are also often considered modulatory as inputs at these locations often cannot cause the neurons to fire but can control the efficacy and plasticity of synaptic inputs closer to the soma. [275] [273] This mechanism potentially affords the finest level of control of plasticity.…”
Section: Control Of Plasticitymentioning
confidence: 99%
“…The distant parts of the dendrites of excitatory neurons in the brain are also often considered modulatory as inputs at these locations often cannot cause the neurons to fire but can control the efficacy and plasticity of synaptic inputs closer to the soma. [275] [273] This mechanism potentially affords the finest level of control of plasticity.…”
Section: Control Of Plasticitymentioning
confidence: 99%
“…Since its theoretical inception in 1970s1718, followed by the establishment of connection with resistance switching behaviour in 2008 (ref. 19), memristive systems have attracted extensive research interests as a disruptive technology for nonvolatile memory92021, in-memory logic22 and brain-inspired computing232425. Depending on the moving ion species, memristive systems can be further classified into electrochemical metallization memory (ECM) driven by the transport of metal cations1326 and valence change memory (VCM) where the resistance switching is presumably caused by the migration of oxygen ions/vacancies92728.…”
mentioning
confidence: 99%
“…It has been found that heterosynaptic plasticity enhances synaptic competition and prevents synaptic weight from going to the extremes to keep the neural network stable. [201,202] In the scheme of three-terminal devices, Yang et al [203] first reported heterosynaptic facilitation in 2015, as shown in Figure 15. Till now, two schemes have been proposed to implement the heterosynaptic plasticity in memristive devices: one is adding another modulatory terminal to the normal pre-/post-synaptic terminal to form three-terminal devices, [200] and the other one is utilizing multiple terminal devices to realize heterosynaptic cooperation and competing.…”
Section: Heterosynaptic Plasticitymentioning
confidence: 99%